Peran Kebudayaan Lokal dalam Membentuk Identitas Generasi Muda di Era Globalisasi: Menekankan fokus pada kebudayaan lokal dan tantangan globalisasi. - Sufi, Ahmad Ibnu (Maliki Interdisciplinary Journal, 2025)
Culture plays a very important role in shaping the identity of Indonesia’s young generation amidst the rapid influence of globalization. However, foreign culture and modernization often erode local cultural values, potentially threatening the sustainability of national identity. This study aims to analyze the role of culture in shaping the identity of the younger generation and identify effective strategies to preserve local cultural values in the era of globalization.This study uses a qualitative approach with a descriptive-analytical method. Data were obtained through in-depth interviews, participatory observation, and literature review, and then analyzed using triangulation techniques. The results showed that local culture contributes significantly in shaping the identity of the younger generation, especially through the values taught in local wisdom-based traditions, arts, and education. However, the main challenges are the lack of cultural integration in the education system and the dominance of digital media that promotes foreign cultures. This research recommends increasing the role of culture-based education, cooperation between cultural communities and the government, and the utilization of digital technology to preserve local culture. The implication of this research is the importance of a holistic approach in maintaining the national identity of the younger generation through adaptive and innovative culture.